2021
DOI: 10.1039/d1ta07599c
|View full text |Cite
|
Sign up to set email alerts
|

Water-steam activation toward oxygen-deficient vanadium oxides for enhancing zinc ion storage

Abstract: A major limitation of vanadium oxides in aqueous Zn/V2O5 ion battery applications is that it suffers from strong Coulombic ion-lattice interactions with divalent Zn2+. Correspondingly, the vanadium oxides endow the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…The XRD result is consistent with the observation of layered structure from SEM measurement. Previous reports have shown that V 2 O 5 with some metal ion intercalation could display purely layered structure by adjusting the experimental parameters accurately, such as LiV 3 O 8 , Ca 0.25 V 2 O 5 , Mg x V 2 O 5 , and AlVO, delivering high energy density and reversibility. ,,,, Similar layered structures have been found for water and aniline molecular intercalated V 2 O 5 materials. ,,− Considering our experimental process and XRD results, it is reasonable to gain primary deduction that the intercalated PANI molecular causes layer spacing of the (001) plane of monoclinic VO 2 to be enlarged from 6.2 Å (14.4°) to 10.2 Å (at 8.7°). However, the phase of L-PANI-VO 2 could not be derived solely by XRD due to the high degree of preferred orientations.…”
Section: Resultssupporting
confidence: 76%
“…The XRD result is consistent with the observation of layered structure from SEM measurement. Previous reports have shown that V 2 O 5 with some metal ion intercalation could display purely layered structure by adjusting the experimental parameters accurately, such as LiV 3 O 8 , Ca 0.25 V 2 O 5 , Mg x V 2 O 5 , and AlVO, delivering high energy density and reversibility. ,,,, Similar layered structures have been found for water and aniline molecular intercalated V 2 O 5 materials. ,,− Considering our experimental process and XRD results, it is reasonable to gain primary deduction that the intercalated PANI molecular causes layer spacing of the (001) plane of monoclinic VO 2 to be enlarged from 6.2 Å (14.4°) to 10.2 Å (at 8.7°). However, the phase of L-PANI-VO 2 could not be derived solely by XRD due to the high degree of preferred orientations.…”
Section: Resultssupporting
confidence: 76%
“…[213,214] The oxygen vacancies were also stated to provide more electrons into the delocalized electron cloud for a higher capacity. [215] Wu et al employed a liquid-exfoliation technique to create a high concentration of oxygen vacancies in bilayer VOPO 4 ⋅2H 2 O (bilayer VOP). [212] Density functional theory showed that this improved conductivity due to the lowered bandgap of ≈0.2 eV (relative to 1.5 eV of the bulk sample) and improved kinetics by lowering the Zn 2+ diffusion energy barrier to ≈0.08 eV from 0.13 eV of the bulk sample when oxygen vacancies were introduced.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[ 213,214 ] The oxygen vacancies were also stated to provide more electrons into the delocalized electron cloud for a higher capacity. [ 215 ] Wu et al. employed a liquid‐exfoliation technique to create a high concentration of oxygen vacancies in bilayer VOPO 4 ⋅2H 2 O (bilayer VOP).…”
Section: High Energy Barrier Of Divalent Zn2+ Cathodic Interactionmentioning
confidence: 99%
“…Particularly, vanadium-based oxides have captured con-siderable attention for ZIB cathodes benefiting from their rich valences and superior theoretical capacity. [20][21][22][23][24][25][26] For example, Yang et al reported that VO 2 (B) nanofibers with tunnel-like frameworks displayed a reversible capacity (357 mA h g −1 at 0.25 C upon 50 cycles). 7 Cheng et al reported that porous V 2 O 5 nanofibers exhibited a sustainable capacity (166 mA h g −1 at 2 C upon 500 cycles).…”
Section: Introductionmentioning
confidence: 99%